2019
DOI: 10.1111/odi.13016
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of temporomandibular disorders and its clinical signs in Chinese students, 1979–2017: A systematic review and meta‐analysis

Abstract: Objective This study intends to assess the prevalence of temporomandibular disorders and its clinical signs in Chinese students. Materials and Methods Search strategies were performed in seven electronic databases, and the reference lists from potentially relevant studies were searched manually. Only observational studies that met the eligibility criteria were selected. A validated instrument was used to evaluate the quality of the included studies. A random‐effects model was used to calculate the pooled preva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 33 publications
2
13
1
Order By: Relevance
“…Female dental students had a higher PHQ-4 mean score than male students which was in agreement with similar studies done on Saudi dental students (Inam 2007, Al-Saleh, Al-Madi et al 2010, Benoliel, Sela et al 2011, Al-Sowygh 2013. Overall, the rate of anxiety in women has been reported to be higher than men (Kessler, Sonnega et al 1995, Steel, Marnane et al 2014, Xie, Lin et al 2019. This could be explained by the slower processing in neurotransmitter serotonin which has a critical role in anxiety and depression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Female dental students had a higher PHQ-4 mean score than male students which was in agreement with similar studies done on Saudi dental students (Inam 2007, Al-Saleh, Al-Madi et al 2010, Benoliel, Sela et al 2011, Al-Sowygh 2013. Overall, the rate of anxiety in women has been reported to be higher than men (Kessler, Sonnega et al 1995, Steel, Marnane et al 2014, Xie, Lin et al 2019. This could be explained by the slower processing in neurotransmitter serotonin which has a critical role in anxiety and depression.…”
Section: Discussionmentioning
confidence: 99%
“…Bagis, Ayaz et al 2012, Naeije, Te Veldhuis et al 2013, Wieckiewicz, Grychowska et al 2014, de Melo Junior, Aroucha et al 2019, Xie, Lin et al 2019, Sankuratri, Verma et al 2021, Srivastava, Shrivastava et al 2021. Interestingly, 30% of the subjects had more than one TMDs diagnosis.…”
mentioning
confidence: 98%
“…Being the third most prevalent social dental disease, TMD affects about 10-15% population across the world and the incidence is still rising (2,3). Typical symptoms of TMD include local pain, limited mandibular movement, and TMJ sounds during movement (4). The etiology of TMD still remains elusive, accumulating evidence suggests that factors from biologic, environmental, social, emotional, and cognitive aspects all play an indispensable role in the occurrence and development of TMD (5).…”
Section: Introductionmentioning
confidence: 99%
“…International epidemiological studies indicated that the prevalence of TMDs affects more than 50% of the world population, where 75% have presented signs at some time, whereas 33% present some symptom and 5% require some type of treatment. [ 1 2 ] It has also been reported that the main origin of this disorder occurs in childhood or adolescence and to a lesser extent in adulthood. [ 3 ] The prevalence of TMDs in Peru is similar to that reported internationally,[ 4 ] so numerous authors in different parts of the world recommend further research to obtain sufficient evidence on this public health problem.…”
Section: Introductionmentioning
confidence: 99%